PENDIDIKAN KELUARGA BAGI PEREMPUAN DALAM PERSPEKTIF ISLAM - Roshiful Aqli Qosyim (Mabahits : Jurnal Hukum Keluarga Islam, 2021)
The religion of Islam was revealed to the world as Rahmatan Lil'alamin, by this means Islam has the meaning that Islam is a religion that brings peace to all mankind. In the perspective of social interaction, there is no discriminatory difference. This status equation is similar to the concept of humanity, namely that basically humans are natural or holy. However, in practice we often observe discriminatory views against women. Women in some societies are considered as the second sex after men. So that their active role in the social world is often neglected and more specifically in the family. This discriminatory view is clearly contrary to the teachings of Islam which is Rahmatan Lil'alamin, and there must be further studies to look at this problem. To provide an understanding with this woman's dignity through the family, because the family is the first educator in the learning process. By starting with the family, it is hoped that family members will have a balanced understanding of the position of women. So looking back at the basic concepts of Islam in the education of women in the family is very important and urgent. For this reason, the author wants to see further how women in Islam actually are.